Health and wellbeing of survivors of sexual violence and abuse attending sexual assault referral centres in England: the MESARCH mixed-methods evaluation - Lorna J O’Doherty; Grace Carter; Emma Sleath; Katherine Brown; Sarah Brown; Eleanor Lutman-White; Louise Jackson; Jon Heron; Priya Tek Kalsi; Olufunmilola C Ladeinde; Dianne Whitfield; Rachel Caswell; et al. (Health and Social Care Delivery Research, 2024)
Background One million people in England and Wales experience sexual violence and abuse each year, with nearly half experiencing serious sexual offences; around 30,000 survivors access sexual assault referral centres. Objectives This research was commissioned by National Institute for Health and Care Research to evaluate access, interventions and care pathways for survivors, especially those provided through sexual assault referral centres. Design, setting, participants The sexual assault referral centres care pathway was investigated through six sub-studies. There were two Cochrane Reviews (4274 participants). Seventy-two providers and 5 survivors were interviewed at eight sites; the children and young people study involved 12 participants from two sexual assault referral centres. A cohort study involving three-wave data collection over 1 year (21 sites; 2602 service users screened, 337 recruited) used a multilevel modelling framework to explore risk factors for burden of post-traumatic stress disorder symptoms at baseline and change at 1 year. We analysed costs and outcomes and conducted a narrative analysis (41 survivors). We worked closely with survivors and prioritised the safety/welfare of participants and researchers. Results Cochrane Reviews identified large effects from psychosocial interventions for post-traumatic stress disorder and depression. Sexual assault referral centres delivered a high-quality frontline service for survivors but groups experiencing domestic abuse and some ethnic and cultural minorities were under-represented. The qualitative research emphasised inter-agency collaboration for survivor benefit. The cohort study identified a risk ‘triad’ of adverse childhood experiences, poor mental health and economic deprivation, which was associated with baseline trauma burden. There were important improvements in trauma symptoms a year later. These improvements were unrelated to different sexual assault referral centre models. Costs and other outcomes were also similar across models. Harmful policing and justice practices/procedures were identified by 25% of participants. In this context, trauma-competent interviewing techniques, regular/timely updates and conveying case decisions with care signalled good practice. Limitations The cohort study lacked a comparison group, reducing confidence in the finding that access to sexual assault referral centres explained the reduction observed in post-traumatic stress disorder. Conclusions and future work Barriers to access call for concerted efforts to implement trauma-informed universal health services. The risk ‘triad’ underscores the value of holistic approaches to care at sexual assault referral centres and timely follow-on care. Poor mental health was the main barrier to service access beyond sexual assault referral centres. The persistence of trauma symptoms a year after accessing sexual assault referral centres signals urgent need for tackling counselling wait-lists, expanding support options and commitment to lifelong care. Multidisciplinary evaluation of sexual assault referral centres for better health provides a foundation for advancing trauma-informed practices in the context of sexual violence and abuse. Study registration This study is registered as ISRCTN30846825 https://doi.org/10.1186/ISRCTN30846825 Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 16/117/04) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 35. See the NIHR Funding and Awards website for further award information. Plain language summary What was the question? Around 30,000 survivors of rape, sexual assault and sexual abuse access sexual assault referral centres in England each year. Sexual assault referral centres provide support, health care and, if people wish, can gather evidence for a criminal investigation. Sexual assault referral centres also open routes to other care/support. We intended to understand the benefits of sexual assault referral centres and ways to improve care. What did we do? We interviewed 72 professionals to understand how they worked together. We followed up 335 survivors over 1 year after visiting a sexual assault referral centre. We gathered the views of 12 children and young people and 41 people from minority and disadvantaged backgrounds. We examined existing research to gather evidence of the benefit of care/support. We worked with survivors to confirm the safety and relevance of our research. What did we find? Participants were positive about sexual assault referral centres and Independent Sexual Violence Advisors, reporting very low harms (1% viewed sexual assault referral centre services as harmful to them). They were also satisfied with charities offering counselling, helplines and advocacy (4% harms). The research gathered mixed feedback about the National Health Service and police, with more harm being reported (15% and 25%, respectively). We found gaps in NHS care for those with complex trauma and long-term mental health problems. Post-traumatic stress disorder affected 70% of participants, with the highest being observed for those with adverse childhood experiences, poor mental health and economic struggles (a risk ‘triad’). Improvements occurred 1 year later, although half of participants still had trauma symptoms. We identified new treatments (e.g. yoga) as potential alternatives to traditional interventions. What does this mean? Sexual assault referral centres offer excellent care to survivors but should be accessible to a wider group of people. Identifying, supporting and careful referral of those with the risk triad mentioned may aid recovery after sexual violence and abuse. The research suggests that the NHS and policing/justice needs to ensure that they provide good care more often. Scientific summary Background Approximately 30,000 victims and survivors of rape, sexual assault and sexual abuse access sexual assault referral centres (SARCs) each year; therefore, there has been an urgent need to assess the experiences of these services. There is also a need to improve options for care; the visibility of and access to SARCs; and collaboration within frontline specialist services to serve people of all ages and genders exposed to sexual assault and rape in England. This research was commissioned by the National Institute for Health and Care Research (NIHR) to evaluate the provision of SARCs. We intended to determine the extent to which SARCs meet the needs of victims and survivors of recent and non-recent sexual violence and abuse, including children, young people and other survivors who may be silenced across different communities in Britain. Objectives The multidisciplinary evaluation of sexual assault referral centres for better health (MESARCH) project addressed a range of research questions, allowing for the evaluation of SARCs and expanding evidence for different services and interventions across SARC care pathways. The questions are as follows: For individuals who have had exposure to sexual violence and abuse, do psychosocial interventions reduce post-traumatic stress disorder (PTSD) and other poor health outcomes? What are providers’ experiences of delivering such psychosocial interventions? What are the experiences of survivors and supporters in accessing such psychosocial interventions? What are the implications of inter-related aspects of SARCs – the everyday work they do, the workforce, the technology and the organisation – for the delivery of SARC services? To what extent are SARCs embedded within the overall response by statutory and voluntary sector organisations to meet the needs of survivors? What are the health and cost trajectories of those who attend SARCs? How can these be compared for different SARC models of service delivery and access to health and Sexual Assault and Abuse Services (SAAS)? What is the effect of different sectors where survivors receive care, including any advantages or disadvantages of accessing post-crisis counselling in the voluntary sector compared with the NHS? What are the experiences of children and young people (CYP) in receiving care and support from SARCs? What do CYP’s recovery journeys look like after receiving support from SARCs? What are the experiences of access to SARCs by survivors with additional vulnerabilities such as chronic mental health problems and survivors from racially and other minoritised populations such as lesbian, gay, bisexual, transgender and/or queer survivors and those with socio-economic deprivation? Methods An innovative focus on patient and public involvement prioritised the safety and welfare of participants and researchers, largely through experts-by-experience embedded across the project lifecycle. A range of mixed-methods was employed: Systematic review, meta-analysis and qualitative evidence synthesis for two Cochrane Reviews For the SARC process evaluation, we mapped out service delivery, undertook thematic analysis of data collected from professionals from a range of SARCs and partners and integrated qualitative data on survivors’ experiences from the cohort study The cohort study interviewed survivors about their health, well-being and service use at baseline, 6 months and 12 months post-SARC. A multilevel modelling framework was used to explore risk factors for PTSD symptoms [Posttraumatic Stress Disorder Checklist for DSM-5 (PCL-5)] (primary outcome) at baseline and reduction in symptoms during the subsequent year; and determine whether SARC service models, service experience and participant-level factors influenced the outcome An economic evaluation based on the costs and changes in health-related quality of life, examining cost per quality-adjusted life-year (QALY) gained at 6 and 12 months Thematic analysis was used in the CYP study A life-narrative method with dialogical narrative analysis was applied in a qualitative study embedded within the cohort study to explore access and recovery experiences of racially minoritised survivors or those disadvantaged by other minoritised identities. Settings of studies in the Cochrane Reviews were health (emergency, primary care) and clinical/therapeutic (mental health), medico-legal (similar to SARCs), universities and community (charity-provided services) and most studies were from the USA. For our primary research, our process evaluation study included eight SARC sites and their inward and onwards partners/professionals; the cohort study followed-up survivors attending 21 SARCs; the CYP study was conducted at two SARCs; the qualitative study included cohort participants and a community (non-SARC) setting. Overall, 24 voluntary sector agencies, a local authority and an NHS sexual health clinic referred people into the sub-studies as our main model of recruitment. The study participants included 72 professionals and 5 survivors from service providers in the process evaluation; 2602 adult service users screened for eligibility through SARCs, 337 of whom joined the cohort study; 34 cohort participants and 7 people from the community (qualitative study); and 12 CYP. Two Cochrane Reviews reported on 4274 survivors, 19 family members and 60 providers. Results A comparative analysis of psychosocial interventions with inactive controls in our Cochrane Review suggests a beneficial effect at post-treatment favouring psychosocial interventions in reducing PTSD [standardised mean difference (SMD) −0.83, 95% confidence interval (CI) −1.22 to −0.44; 16 studies, 1130 participants; low‐certainty evidence; large effect size based on Cohen’s d] and depression (SMD −0.82, 95% CI −1.17 to −0.48; 12 studies, 901 participants; low‐certainty evidence; large effect size). The main comparative analysis did not detect unwanted effects from interventions. Our complementary Cochrane Review revealed that interventions helped survivors to better understand trauma and its effects, re-engage in many areas of life and improve interpersonal functioning. ‘Readiness’ was vital for engagement and may be as important as intervention content. Empowering survivors (and supporters) to make decisions about their interventions, for instance, having control over when they start and end interventions, was an important step in recovery. Our process evaluation study showed that SARCs remain an underutilised care pathway for survivors, exacerbated by lack of awareness in the general public, and thus survivors. Routes to SARC care are well-established among police forces, but poorly developed across some other professional groups (e.g. general practitioners [GPs]). Statutory and voluntary sector organisations working in partnership provides enhanced care for survivors, but SARCs and other organisations are hampered by a range of organisational and commissioning structures and processes. Service users joined the cohort study (with a baseline interview) 100 days after they had accessed a SARC (median = 104 days). They met the inclusion criteria of being ≥ 18 years and having sought assistance from a SARC after sexual violence and abuse (index exposure). This abuse was perpetrated by acquaintances (40%), strangers (20%) and partners (25%) and during childhood (13%). Forty-four per cent of the participants accessed a SARC within 10 days of trauma exposure; 38% underwent a forensic medical examination, and 85% had accessed Independent Sexual Violence Advisor (ISVA) care at baseline. Cohort participants were mainly women (90%), belonged to non-minoritised ethnicities (85%), had a mean age of 32 years (range: 18–75 years) and reported a high burden of lifetime trauma [77% indicated four or more adverse childhood experiences (ACEs) and 80% had prior exposure to domestic abuse]. Seventeen per cent of the users faced major daily financial problems. Nearly half of them had pre-existing mental health problems at the point of accessing SARC, and more than half had attempted suicide. Between SARC access and baseline, 56% had been prescribed psychotropic medications and had an average of 20 contacts with health/social/third-sector care [21 contacts at 6 months (a longer timeframe), dropping to 13 at 12 months]. At baseline, 71% of participants had ‘probable PTSD’, decreasing to 55% at 1 year. This reflected an unadjusted mean reduction of 9 points on PCL-5 (95% CI 6.6 to 11, Cohen’s d = 0.53), equating to a clinically important within-group change. One-third of the original cohort was lost to follow-up at 1 year, differing from those retained only on having greater socio-economic deprivation. The study did not detect differences in outcomes at 1 year according to the type of SARC service model (there were four types) they accessed or the location of the ISVA (some ISVAs are part of the SARC team and others are located in the community). There was strong evidence of a positive association between service use and symptom level at baseline, with a one-unit increase in the log of service use count being associated with a 4.5-point higher symptom score at baseline (95% CI 2.6 to 6.4; p < 0.001). For participant-level factors, each additional ACE was associated with a 1.4-point greater score of PTSD symptoms (95% CI 0.8 to 1.9; p < 0.001) and pre-existing mental health problems, with a 7.6-point difference (95% CI 4.0 to 11.1; p < 0.001). Participants with greater financial resources had fewer symptoms than for those with smaller financial resources (p = 0.009). Additionally, there was strong evidence that being unable to work was associated with a 10-point higher baseline score (p < 0.001). For offence-related factors, there was weak evidence that a delay to SARC of more than 10 days was associated with an approximately 4.5-point greater symptom score (p = 0.087), and a similar level of evidence was observed for an association for perpetrator type, where it appears that when the perpetrator was the survivor’s partner/family member, the baseline symptom score was greater. The main predictor of PTSD at 12 months was the baseline score. A high ACE profile doubled the odds of meeting the PTSD diagnostic threshold at baseline, but it reduced to 1.5 at 6 months and was absent at 1 year. SARCs and third-sector agencies achieved consistently high standards of care for survivors across sub-studies, with 50% of participants submitting ratings for these sectors as ≥ 90 on a harm-benefit scale [−100 to 100]. However, harmful responses were much more common in statutory health and justice settings, affecting 15% and 25% of participants, respectively (compared with 1% for SARCs and 4% for the third sector). The children and young people study observed that recovery and healing was influenced by how quickly the CYP accessed support, its content and duration, the location and context of care, how well the services worked together and CYP’s interactions with professionals at SARCs and across sectors. The embedded narrative study identified vital issues around access, as well as risk and recovery, in particular, inequalities arising from chronic mental health, economic disadvantage and family/community-based abuse highly mirroring the risk triad identified in the cohort study. Consistent support for survivors from all professionals and organisations a survivor engages with, ability to move away from the location where abuse has occurred and the opportunity to keep trying different therapies or activities supporting recovery were identified as helpful approaches to the recovery journey. Conclusions Sexual assault referral centres must recognise the high burden of lifetime trauma and chronic mental problems that affect most service users accessing this service. There is evidence that these factors, together with socio-economic status, affect people’s PTSD presentation to a greater degree than aspects of the offence (perpetrator and time since trauma), although these were still important. Different types of SARC and ISVA models did not appear to impinge on trauma symptoms at 1 year, or the way in which survivors experienced care within the SARC and onwards support agencies. Survivor service use was positively related to baseline trauma, which decreased over time, and costs did not differ according to the type of SARC or ISVA service accessed. This emphasises the importance of raising the visibility of SARCs as a care route overall, rather than recommending a specific model of delivery. The SARC pathway may deliver benefits to survivors who report clinically important reductions over time, especially among those with the greatest burden. However, half of the study sample participants remained positive for PTSD at 1 year. Every recovery journey following a sexual assault or abuse is different, and both formal and informal sources of support are important. A consistent trauma-informed societal response to sexual violence is needed. For CYP, early support from SARCs and accessible trauma-informed support throughout adolescence and into adulthood was critical in young people’s recovery. Implications for health care Sexual assault referral centre services deliver a high-quality frontline service for survivors and an effective gateway to health, ISVAs and voluntary sector services. A triad of lifetime traumas, chronic mental health problems and economic deprivation is apparent, which highlights the potential for holistic approaches at SARCs. Enquiring about a wide range of background factors may enhance timely access to appropriate therapies (see our Cochrane Reviews) as well as to social care and advocacy for housing, finances and domestic abuse, as part of the multipronged approach to support recovery and healing among survivors of sexual violence and abuse. Mental health difficulties represented the main barrier to accessing services beyond SARCs, and people affected struggled to consistently access the primary and therapeutic care they needed in the NHS as well as engagement with justice, calling for dedicated ISVA resources with mental health specialism. Inequalities are exacerbated in situations where survivors with relevant resources have the ability to pay for the therapeutic care they need and those without resources do not have the ability to pay and are left waiting. The findings on risk facing racially and other minoritised groups call for concerted efforts to support people to reach care through outreach programmes and campaigns and implement trauma-informed universal health services. Narratives of racial and cultural discrimination by services were not dominant in our qualitative enquiry, but a profound damage was reported when discrimination had occurred. There are vital interconnections between experiences of justice and health outcomes in this context. Harm in police and justice settings was marked, and calls for ongoing efforts to improve communication and other practices by the police in this context are warranted. Our data identified the good practice witnessed, and narratives containing practical measures agencies can take to minimise harms and enhance experiences of justice. We found support for cohesive commissioning strategies that promote a collaborative whole-systems approach to meeting the wide-ranging needs of people after exposure to sexual violence and abuse. The research evidences important improvements in trauma symptoms, but symptoms persisted for many participants at 1 year, supporting calls for tackling wait-lists, enhancing the therapy offering and a commitment to lifelong care for survivors of sexual violence and abuse. Working with survivor stakeholders at all research levels has been demonstrated to enhance feasibility of research and was experienced as empowering by survivor participants; this ethos should be translated into practice settings to diagnose barriers to meeting survivors’ needs and promote services improvement. Future research must focus on expanding evidence for interventions and developing professional interventions for enhancing trauma-informed practice. The MESARCH project identified strengths and urgent gaps in health and justice provision for survivors, and the findings provide a foundation for advancing trauma-informed practices when providing care to and supporting people exposed to the damaging effects of sexual violence and abuse. Study registration This study is registered as ISRCTN30846825 https://doi.org/10.1186/ISRCTN30846825 Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 16/117/04) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 35. See the NIHR Funding and Awards website for further award information.